Fish Cognition and Behavior 2011
DOI: 10.1002/9781444342536.ch6
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Behaviour in Fish: Integrating Information about Contest Costs

Abstract: As the introductory chapter to the first edition of this book (Brown et al. 2006) noted, fish behaviour has long been viewed as stereotyped and not strongly influenced by context or experience. The recognition that experience and learning can influence fish behaviour coupled with observations of considerable variation in behaviour within and between individuals has led to an increasing awareness of the complexity of fish behaviour. Behavioural ecologists are interested in understanding the causes and effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 137 publications
2
13
1
Order By: Relevance
“…Our third experiment clearly showed that winner/loser effects do not operate in this species. In our fourth experiment, the operation of social eavesdropping alone was ruled out, as we observed no differences in the responses of the observing fish against winner of an observed contest (Oliveira et al, 1998;Hsu et al, 2006Hsu et al, , 2011. In Experiment 5, the focal male (B), which had no direct contact with the winning male (C) behaved submissively against C in test phase, suggesting transitive inference by the focal male.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…Our third experiment clearly showed that winner/loser effects do not operate in this species. In our fourth experiment, the operation of social eavesdropping alone was ruled out, as we observed no differences in the responses of the observing fish against winner of an observed contest (Oliveira et al, 1998;Hsu et al, 2006Hsu et al, , 2011. In Experiment 5, the focal male (B), which had no direct contact with the winning male (C) behaved submissively against C in test phase, suggesting transitive inference by the focal male.…”
Section: Discussionmentioning
confidence: 76%
“…Any effects of physical characteristics on competition outcomes can also be ruled out because fish were of equal size and sex, and there are no other phenotypic indicators of dominance in this species (e.g., "status badges"; Møller, 1987;Beani and Turillazzi, 1999). Thus, our fifth experiment shows that male J. transcriptus infer the relative social status of an unknown stranger without physical interaction, using transitive inference (Whitehouse, 1997;Hsu et al, 2006Hsu et al, , 2011Oliveira et al, 2009). …”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations